Liquid antipsychotics in the management of psychomotor agitation: a focus on promazine - Marta Matrone; Alessandro Cuomo; Sergio De Filippis; Andrea Fagiolini; Mario Amore (BioExcel Publishing Ltd, 2024)
Psychomotor agitation (PMA) is a prominent clinical issue frequently observed in various psychiatric and neurological conditions, including schizophrenia, bipolar disorder, Parkinson disease, dementia and substance use disorder. Characterized by motor restlessness, anxiety and irritability, PMA can rapidly escalate into aggression and violence, necessitating prompt intervention to ensure patient and caregiver safety. The prevalence of PMA in psychiatric emergency settings ranges from 4.3% to 10%, imposing a substantial burden on healthcare systems. Despite the critical nature of PMA, there is a lack of standardized treatment protocols, particularly concerning the use of liquid formulations of antipsychotics such as liquid promazine, which may offer unique advantages in emergency care. This review aims to provide a comprehensive analysis of the existing literature on the efficacy, safety and tolerability of liquid antipsychotics, with a particular focus on promazine, in the management of PMA. An extensive literature search was conducted across publicly available databases with no time limitations to ensure the inclusion of all relevant articles. The findings suggest that liquid promazine offers several benefits, including ease of administration, rapid onset of action and improved patient compliance, making it a valuable option in acute PMA management. However, the review also highlights the need for future research, particularly long-term studies and head-to-head comparisons with other antipsychotics, to better establish the clinical utility of liquid promazine. Future research should focus on expanding the evidence base for liquid antipsychotic formulations, which will contribute to improved clinical outcomes in the management of PMA.